Integrasi Ilmu Turath dan Saintifik dalam Penyelidikan Sebagai Prakarsa Dakwah Kontemporari - Muhammad Remy Othman; Mohd Farhan Md Ariffin; Sayidah Asma Basir; Khadher Ahmad; Zulkifli Mohd Yusoff; Khalijah Awang (USIM Press, 2024)
Vol. 27 (2022) Page (68-80)